Identification and mechanistic studies of novel antibiotic resistance modifying compounds from lavender essential oil against carbapenemase-producing Klebsiella pneumoniae - Yang, Shun Kai (2019)
Carbapenemase-producing Klebsiella pneumoniae (KPC-KP) remains the most notorious nosocomial pathogen due to resistance towards all β-lactam antibiotics. Mining of novel antimicrobials, especially from essential oils are crucial to address this issue. Hence, this study was undertaken to identify and elucidate the mode of action of novel antimicrobial agents from essential oils. From the preliminary screening of five essential oils, lavender essential oil (LVO) reacted synergistically with meropenem, reducing the effective dosage of LVO from 10% to 0.63% and meropenem from 32 μg/mL to 8 μg/mL. The other four essential oils reacted additively with meropenem with cinnamon bark essential oil (CBO) having the highest degree of additivity, reducing the effective dosage of CBO from 0.16% to 0.08% and meropenem from 32 μg/mL to 16 μg/mL. Comparative proteomic analysis suggested membrane disruption, as indicated by reduced abundance of membrane and cytoplasmic proteins in LVO- and CBO-treated KPC-KP cells. Upregulation of oxidative stress regulator and downregulation of oxidative stress-sensitive proteins indicates presence of oxidative stress upon exposure to essential oil, explaining the membrane disruption phenomena via lipid peroxidation. Membrane disruption assays, namely zeta potential measurement, outer membrane permeability assay and scanning electron microscopy was performed to validate the membrane disruption speculation. It was observed that exposure to LVO and CBO increases the membrane zeta potential and membrane permeability of KPC-KP cells. Membrane disruption can also be seen in the scanning electron microscopy with corrugated bacterial surface. The results strongly suggest that LVO and CBO disrupt the bacterial membrane via induction of oxidative stress. Comparative studies between additive and synergistic interaction revealed that additivity interaction (CBO-meropenem) are slightly inferior when compared to the synergistic combinations (LVO-meropenem) in terms of membrane disruption. LVO was selected for further analysis involving the identification of antimicrobial compounds. GC-MS analysis identified 32 compounds; β-caryophyllene (BCP), borneol (BNO), linalool (LOL) and linalyl anthranilate (LNA) were selected for antimicrobial screening based on composition percentage. It was found that only LNA and LOL were bioactive against KPCKP cells; both reacted additively to meropenem. Comparative proteomic analysis performed revealed similar results as LVO, showing low abundance of membrane and cytoplasmic proteins, suggesting membrane disruption. Upregulation of oxidative stress regulator and downregulation of oxidative stress-sensitive proteins indicates the presence of oxidative stress which leads to lipid peroxidation and membrane disruption. Zeta potential measurements revealed an increase in membrane charge while the outer membrane assay showed an increase in membrane permeability in KPC-KP cells treated with LNA, LOL and LNA-LOL. Electron microscopy showed both compounds had significant role in disrupting the bacterial membrane which leads to intracellular leakage and cell death. Compounds were subjected to cytotoxicology evaluation via the MTT assay; results showed that the combination of LNA and LOL are relatively less toxic to HepG2 cell lines in comparison to individual compound. In conclusion, this study explained the mechanism of LVO and CBO, LNA and LOL on bacterial membrane disruptions together with cytotoxicity evaluation of compounds against HepG2 cells. The findings would be helpful in future application of LNA and LOL as novel antimicrobial agents in clinical settings.